Choosing Between School Systems - Volker Meier (Center for Economic Studies and ifo Institute (CESifo), 2000)
Hierarchical and comprehensive school systems are compared with respect to efficiency. At given ability, a student's probability of not completing school rises with increasing mean ability in class. Both school systems can yield identical average failure rates. Given that output losses in case of failure are stronger for more talented students, the comprehensive school system will generally lead to a higher total income.
Keywords: 330; Education; school system